2012
DOI: 10.1111/j.1467-9817.2012.01536.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between spontaneous note‐taking, self‐reported strategies and comprehension when reading multiple texts in different task conditions

Abstract: This study investigated note‐taking during multiple‐text reading across two different task conditions in relation to comprehension performance and self‐reports of strategy use. Forty‐four undergraduates read multiple texts about climate change to write an argument or a summary. Analysis of students’ spontaneous note‐taking during reading showed that intertextual elaboration strategies, as indicated by the notes, were related to deeper‐level, integrated comprehension for students reading to construct an argumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 41 publications
2
35
1
6
Order By: Relevance
“…'s () model, then, our findings suggest that trying to comprehend each text in isolation is a less viable approach when reading multiple documents on the same issue. Rather, students who act on their beliefs to note different sources and elaborate across them seem to be better off in such a complex reading‐task context, as also corroborated by several other recent studies showing the importance of integrative processing during multiple‐documents reading (e.g., Goldman, Braasch, Wiley, Graesser, & Brodowinska, ; Hagen, Braasch, & Bråten, ).…”
Section: Discussionsupporting
confidence: 72%
“…'s () model, then, our findings suggest that trying to comprehend each text in isolation is a less viable approach when reading multiple documents on the same issue. Rather, students who act on their beliefs to note different sources and elaborate across them seem to be better off in such a complex reading‐task context, as also corroborated by several other recent studies showing the importance of integrative processing during multiple‐documents reading (e.g., Goldman, Braasch, Wiley, Graesser, & Brodowinska, ; Hagen, Braasch, & Bråten, ).…”
Section: Discussionsupporting
confidence: 72%
“…Consistent with this proposal, ample empirical evidence has shown that reading tasks influence text-processing strategies (e.g., Hagen et al 2014;Lorch et al 1993;Narvaez et al 1999;van den Broek et al 2001) and subsequent comprehension outcomes (e.g. Bråten and Strømsø 2010;Britt and Sommer 2004;Gil et al 2010;Richter 2003).…”
Section: Reading Task and Multiple Text Comprehensionmentioning
confidence: 80%
“…To the best of our knowledge, only one study in the field of multiple text comprehension addressed reading comprehension strategies triggered by argument vs. summary tasks using note-taking as an indicator of strategy use (Hagen et al 2014). Hagen and colleagues found no general differences in the use of reading strategies (paraphrases, intertextual, and intratextual elaborations) between the argument and summary conditions.…”
Section: Effects Of Reading Tasks On the Strategic Processing Of Multmentioning
confidence: 99%
“…This distinction, though, is important, as producing a 'summary' (distilling claims from documents) versus an 'argument' (justifying stances on claims from documents) produces different kinds of behavior -including in mediating the kind of talk aloud or collaborative dialogue students engage in -as well as end product (Bråten & Strømsø, 2009;Cho, Lee, & Jonassen, 2011;Gil, Bråten, Vidal-Abarca, & Strømsø, 2010;Hagen, Braasch, & Bråten, 2012).…”
Section: Information Seeking Credibility Assessment Behavioursmentioning
confidence: 99%